Combining Magma Flow and Deformation Modeling to Explain Observed Changes in Tilt - Marsden, Luke H.; Neuberg, Jürgen W.; Thomas, Mark E.; Mothes, Patricia A.; Ruiz, Mario C. (Frontiers in Earth Science, 2019)
The understanding of magma ascent dynamics is essential in forecasting the scale, style and timing of volcanic eruptions. The monitoring of near-field deformation is widely used to gain insight into these dynamics, and has been linked to stress changes in the upper conduit. The ascent of magma through the conduit exerts shear stress on the conduit wall, pulling up the surrounding edifice, whilst overpressure in the upper conduit pushes the surrounding edifice outwards. H\sout{owever, h}ow much shear stress and pressure is produced during magma ascent, and the relative contribution of each to the deformation, \sout{is yet to be fully understood and quantified}\textcolor{blue}{has until now only been explored conceptually}. By combining flow and deformation modelling using COMSOL Multiphysics, we \sout{are} for the first time \sout{able to}\textcolor{blue}{present a quantitative model that links magma ascent to deformation. We} quantify how both shear stress and pressure vary spatially within a conduit, and show that shear stress generally dominates observed changes in tilt close to the conduit during activity at Tungurahua volcano, Ecuador, between 2013 and 2014. However, the relative contribution of pressure is not insignificant, and \sout{the full stress tensor comprising} both pressure and shear stress must be considered when interpreting deformation data. We demonstrate that significant changes in tilt \sout{can occur as magma refills an empty conduit, or} can be driven by changes in the driving pressure gradient or volatile content of the magma. The relative contribution of shear stress and pressure to the tilt varies considerably depending on these parameters. Our work provides insight into the range of elastic moduli that should be considered when modelling edifice-scale rock masses, and we show that even where the edifice is modelled as weak, shear stress \textcolor{blue}{generally} dominates the near field deformation over pressurisation of the conduit.